Critical Success Factors of the University of the Future in a Society 5.0: A Maturity Model. (December 2020) - Panizzon, Mateus; Barcellos, Paulo Fernando Pinto
When addressing the possible futures for the university, one can ask what the new critical success factors (CSF) are that represent the core of the University of the Future, from a strategic perspective of analysis. Considering the Society 5.0 paradigm, characterized by higher levels of uncertainty, turbulence, and balance between technology and human values, adaptation to the ecosystem becomes an essential competence. Based on the literature, considering the convergence of organizational cybernetics and biomimetics, this theoretical article proposes a set of new CSF for the University of the Future, expanding the analysis of Society 5.0 and the future challenges for universities. Additionally, proposes a maturity model with eleven dimensions and three stages to support this discussion, visioning a future scenario. This foresight approach provides new insights to think over strategic critical success factors for the university to respond to possible and sustainable futures. Reconfiguration, purpose, and digitization are capacities to address the new environment set in this Smart Society. With this analysis, strategic questions are proposed for researchers and practitioners, especially to address global and regional challenges that universities will face, particularly due to the technological gap established between countries.